Development and Adjustment of an Algorithm for Identifying Drug-Related Hospital Admissions in Pediatrics - Schulze, Christopher; Toni, Irmgard; Moritz, Katrin; Eberl, Sonja; Rascher, Wolfgang; Neubert, Antje (Journal of Patient Safety, 2022)
Objective Adverse drug events (ADEs) in the outpatient pediatric pharmacotherapy can be serious and lead to inpatient admissions. Recent research only focused on ADE identification during hospitalization. The aim of the present study was to develop an algorithm to identify drug-related hospital admissions in pediatrics. Methods A systematic literature research was performed, and a pediatric trigger tool for identifying drug-related inpatient admissions was built. The initial version was tested in a sample of 292 patients admitted to a German university children's hospital. Subsequently, the tool was further improved by combining different modules as a novel approach. Results The obtained algorithm with 39 triggers in 5 modules identified drug-related inpatient admissions at a sensitivity of 95.5% (95% confidence interval [CI], 89.3%-100%) and a specificity of 16.5% (95% CI, 11.9%-21.2%), respectively. After modifications including trigger activation requiring a combination of different modules, specificity increased to 56.9% (95% CI, 50.7%-63.0%). Identifying 36 of 44 ADEs leading to admission, sensitivity remained high (81.8% [95% CI, 70.4%-93.2%]). The overall positive predictive value was 25.2% (95% CI, 18.1%-32.3%). Conclusions The algorithm is the first trigger tool to identify ambulant acquired ADEs leading to hospital admission in pediatrics. However, the underlying patient sample is small. Using a larger population for refinement will allow further specifications and reduction in the total amount of triggers and thus signals.
CRIS-Team WoS Importer:2022-08-26

Drug Utilisation and Off-Label Use on a German Neonatal Intensive Care Unit: A Retrospective Cohort Study and 10-Year Comparison - Geißler, Carmen; Schulze, Christopher; Botzenhardt, Sebastian; Rascher, Wolfgang; Neubert, Antje (Pharmacy, 2020)
Pharmacotherapy of neonates is complex and marked to a large extent of off-label use. The implementation of the Paediatric Regulation (2007) gave hope for a change in the safety and efficacy for drugs used in neonatal intensive care units (NICU). This study investigates drug utilisation patterns and off-label use in a German neonatal intensive care unit (NICU) in 2014. A 12-months retrospective, observational cohort study was performed at the NICU of the University Children's Hospital Erlangen, Germany. Licensing status was determined using the Summary of Product Characteristics (SmPC). Results are compared with a similar study conducted 10 years earlier. The study included 204 patients (57.8% male) (2004: 183) and 2274 drug prescriptions were recorded (2004: 1978). The drugs that were mostly prescribed were drugs for the nervous system (2004: 22.6%; 2014: 26.9%) and anti-infectives for systemic use (2004: 26.0%; 2014: 24.9%);34.3% (2004) and 39.2% (2014) of all prescriptions were off-label;62.7% of all patients received at least one off-label or unlicensed drug (2004: 70%). For 13 drugs, the licensing status changed either from off-label to label (n = 9) or vice versa (n = 4). Overall, there was no significant change neither in terms of the drugs used nor regarding their licensing status. Further studies are needed to validate these findings in a European context.
CRIS-Team WoS Importer:2020-10-30

Oral Presentation: Drug-Related Hospital Admissions in Paediatrics-Is There Potential for Prevention? - Toni, Irmgard; Ahne, G.; Marek, Ines; Moritz, Katrin; Schulze, Christopher; Schreeck, F.; Makosi, D. M.; Rascher, Wolfgang; Neubert, Antje (DRUG SAFETY, 2022)
CRIS-Team WoS Importer:2022-10-07

Self-medication in children under the aspect of medication safety Selbstmedikation bei Kindern unter dem Aspekt der Arzneimitteltherapiesicherheit - Neubert, Antje; Schulze, Christopher (Monatsschrift Kinderheilkunde, 2022)
Background: Self-medication, also known as over the counter (OTC) medication, is generally understood as the use of drugs that do not require a doctor’s prescription. It is very often used for colds or pain and fever; however, the OTC status does not mean, as is often assumed, that these drugs can be used completely uncritically. Especially in children and adolescents, serious side effects repeatedly occur. Objective: This article investigates which drugs are often used in self-medication and describes which problems can arise in association with different indications. Material and methods: The article is based on a search and analysis of the current literature. Results and discussion: The most commonly used OTC drugs are cough and cold medicines, medicines used to treat pain and fever and medicines used to treat nausea. Herbal preparations play an important role in self-medication for cold remedies; however, these multisubstance preparations are not always harmless and, especially with combination therapies, a doctor or pharmacist should always be consulted. In addition, the use of both herbal and synthetic preparations is based on very limited scientific evidence. Decongestant preparations for the nose and drugs against nausea (H1 antihistamines) have been and are repeatedly associated with serious adverse effects, especially in young children and should therefore be used strictly according to the license. Pain and fever can be treated very well with ibuprofen or paracetamol. Monotherapy should always be preferred for self-medication.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Adverse effects; Nonprescription drugs; Over the counter drugs; Plant preparations; Synthetic drugs